Subgeneric placement of Otiorhynchus tomentifer Boheman, 1842 (Coleoptera: Curculionidae: Entiminae), a new senior synonym of Otiorhynchus semitarius Reitter, 1913 - Yunakov, Nikolai; Khrapov, Denys (Zootaxa, 2023)
Otiorhynchus tomentifer Boheman, 1842 is redescribed, and its new placement in the subgenus Pseudocryphiphorus Magnano, 1998 is proposed. The placement of O. tomentifer in the subgenus Postaremus Reitter, 1912 is rejected. Otiorhynchus semitarius Reitter, 1913 is a new junior synonym of O. tomentifer Boheman, 1842. Comprehensive morphological data on female and male genitalia, including the endophallic structures of O. tomentifer and O. nodosus (Müller, 1764), the type species of the subgenus Postaremus, are given.